Detection of regions of homozygosity in an unusual case of frontonasal dysplasia - César Paz-y-Miño; Ramón Miguel Vargas-Vera; Martha Verónica Placencia-Ibadango; Kalid Stefano Vargas-Silva; Juan Luis García-Hernández; Thalía Balarezo-Díaz; Paola E. Leone (Molecular Cytogenetics)
Abstract We present the case of a 7-year-old Ecuadorian mestizo girl with multiple orofacial malformations. The patient is the product of a first-degree relationship (father–daughter). A cytogenetic study revealed a normal karyotype. The genetic mapping array study identified 0.73 Gb of alterations, 727,087,295 bp involved in regions of homozygosity (ROH) in all chromosomes (25.2% of the genome) and 764,028 bp in gains in chromosomes 9 and 14. Genes from the TGFB, BMP, FGF, SHH and WNT families, among others, were identified in the ROH. They are related to craniofacial development and their protein products showed a strong association in the interactome analysis.